The cross-cultural generalizability of the psychopathy checklist: Youth version for adjudicated indigenous youth - McCuish, Evan C. (Author); Mathesius, Jeffrey R. (mathesiusj) (Author); Lussier, Patrick (Author); Corrado, Raymond R. (Author); (Author) (Psychological Assessment, 2018)
There is a paucity of Indigenous-specific research examining the reliability and validity of assessment tools routinely utilized within the justice system. Evaluating the cross-cultural reliability and validity of such tools is important for establishing generalizability as part of ethical practices; this is particularly important to address within Canada’s Indigenous youth population because of longstanding effects of colonization, structural adversities, and overrepresentation in the youth justice system and the possible long-term impact of improper assessment on adult outcomes. A step toward this aim was undertaken in the current study by comparing scale reliability, structural validity, measurement invariance, and predictive validity of the Psychopathy Checklist: Youth Version (PCL:YV) across Indigenous (n = 137) and White (n = 312) adjudicated youth. Polychoric ordinal alpha values indicated that PCL:YV test score scale reliability was high for both Indigenous and White youth. Confirmatory factor analyses demonstrated that a 3-factor and 4-factor model provided acceptable-to-good fit for the full sample, and an examination of configural, metric, and scalar measurement invariance illustrated that both factor structures fit the subsamples equally well. PCL:YV test scores were also moderately associated with measures of different offending outcomes and performed similarly across White and Indigenous participants. Overall, support was found for the use of the PCL:YV within Indigenous youth, including its use in conjunction with other risk factors and assessment tools to guide risk assessment decisions for this group. The importance of cross-cultural research and directions for future research are discussed. (APA PsycInfo Database Record). Peer reviewed Final article published cross-cultural research indigenous youth PCL psychopathy YV